Analysis and measurement of the impact of small projects on poverty in Iraq for the period (2004-2024) - Qader, Asst.L.Idris Ahmed Saleh; Suleiman, Asst.L.Bakhan Qadir; Abdullah, Asst.L.Ako Khadr (Sulaimani Journal for Humanities, 2026)
This research aims to highlight the contributions of small businesses and demonstrate their important and positive role in combating poverty, a phenomenon considered one of the economic and social problems faced by both developed and developing societies. This is due to their flexibility in providing job opportunities within the business community, as well as their role in national development and their reliance on individual initiatives. This research aims to demonstrate the impact of small businesses on poverty in Iraq during the period (2004-2024). To achieve this objective, a descriptive and econometric analytical approach was used, relying on official data, figures, information, and graphs published on the websites of the Central Bank of Iraq, the Ministry of Finance, and the Iraqi Ministry of Planning. In the applied aspect, the econometric method and the ARDL model were used to measure relationships in both the short and long term. The research concludes that there is an inverse relationship between small businesses and poverty rates; the greater the number of small businesses, the lower the poverty rates will be in both the short and long term. It proposes working to create an integrated and flexible financing system that allows projects to obtain the necessary financial support for establishment and development, drawing up a strategy and identifying appropriate mechanisms to provide interest-free loans to finance projects while taking into account the specificities of Iraqi (Muslim) society, and giving more freedom and incentives to state-owned banks and lending institutions to encourage them to lend to the private sector.
Keywords: Small businesses; poverty; project financing; the economic problem